Analisis Corporate Governance dalam Kemitraan Pemerintah dan Badan Usaha Bidang Infrastruktur - Tyahya Whisnu Hendratni; Hindradjid Harsono; DW Soemarsono (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2021)
The purpose of the study was to determine: The influence of Corporate Governance in the Government and Business Entity Partnership (PPP) in the infrastructure sector, the main factors that can affect the Government and Business Entity Partnership (PPP) in the Infrastructure sector and How to apply the principles of Corporate Governance in the Government and Business Entity Partnership ( PPP ) in the infrastructure sector in Indonesia. The population and subjects studied are a group of people who understand the Government and Business Entity Partnership (PPP), namely from the Association of Professional Experts on Government Partnerships and Indonesian Business Entities (PAP-KPBUI) as many as 142 people. For data analysis used in this study use Ordinary Least Square (OLS) regression estimation technique to analyze the relationship between the independent variable and the dependent variable. Data processing is carried out using SPSS 23. The results of the study can be seen that the variables of Transparency, Accountability, Responsibility, Independence, and Justice together have a contribution of influence of PPP in the Infrastructure sector.